Acquired port-wine stain. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
We observed a child of 2 years and 5 months (Fig. 4) with flat angiomatous lesions of the first and second left trigeminal branch. The eye examination showed no signs of glaucoma. The brain MRI showed meningeal changes compatible with Sturge-Weber syndrome. These data led to the diagnosis of port-wine stain of the 1st and 2nd left trigeminal branch. We asked the mother confirmation of the presence of lesions at birth, but the mother not only categorically denied their presence at birth, but provided photo-documentation showing that at 72 days of age (Fig. 1) there was not lesion, that the first lesions had appeared in the fourth month of life (Fig. 2) and that then had become more visible at 12 (Fig. 3) and 29 (Fig. 4) months. The final diagnosis was acquired port-wine stain. The mother ruled out traumas preceding the appearance of the lesions.